2002
DOI: 10.1002/ajmg.10500
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic spine and dendritic field characteristics of layer V pyramidal neurons in the visual cortex of fragile‐X knockout mice

Abstract: Fragile-X syndrome is a common form of mental retardation resulting from the inability to produce the fragile-X mental retardation protein. The specific function of this protein is unknown; however, it has been proposed to play a role in developmental synaptic plasticity. Examination of human brain autopsy material has shown that fragile-X patients exhibit abnormalities in dendritic spine structure and number, suggesting a failure of normal developmental dendritic spine maturation and pruning in this syndrome.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
221
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 247 publications
(242 citation statements)
references
References 23 publications
17
221
4
Order By: Relevance
“…These mice show immature dendritic spine morphology similar to that observed in human fragile X patients (4,31). Here, we investigate rapid neurotransmitter-induced translation in synaptoneurosomes of fmr1-KO and WT mice.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…These mice show immature dendritic spine morphology similar to that observed in human fragile X patients (4,31). Here, we investigate rapid neurotransmitter-induced translation in synaptoneurosomes of fmr1-KO and WT mice.…”
mentioning
confidence: 78%
“…Because of the abnormal dendritic spine morphology observed in human fragile X patients and fmr1-KO mice (3,4,31,38), we next considered whether postsynaptic compartments in KO mice might reseal into smaller synaptic structures than those of WT mice, altering the probability that they contain translation components. Synaptoneurosome preparations were examined by electron microscopy for possible differences in the size or shape of the postsynaptic components.…”
Section: More Cortical Spine Synapses Have Polyribosomes In Wt Than Inmentioning
confidence: 99%
“…However, at the single-neuron level (using the Golgi impregnation technique on postmortem brain tissue), cortical neurons in several regions have abnormal dendrites, with spines showing excessive numbers and length [Rudelli et al, 1985;Hinton et al, 1991;Wisniewski et al, 1991;Irwin et al, 2001]. Similar studies in the Fmr1 mutant mouse confirmed these findings, as well as excessive dendritic branching [Comery et al, 1997;Irwin et al, 2002;Galvez et al, 2003]. Given that spines are postsynaptic sites and that dendrites undergo complex alterations during development [Cline, 2001], it is not surprising that a "subtle" morphological change would cause serious functional consequences.…”
Section: Case In Point: Drosophila Fragile X Mental Retardation 1 (Dfmentioning
confidence: 92%
“…Observations in post-mortem tissue from individuals with FXS and in the Fmr1 KO mouse have shown that functional deletion of FMRP leads to increased density of filopodia-like and immature dendritic spines (Irwin et al, 2001(Irwin et al, , 2002, suggesting an important role of FMRP for dendritic spine development and maintenance. The analyzed parameters and the described dendritic spine abnormalities vary between different reports.…”
Section: Abnormal Dendritic Spine Morphology In Fxsmentioning
confidence: 99%
“…They include in vivo and in vitro studies, as well as analyses of dendritic protrusion and filopodia density, dendritic spine classification, and dendritic arborization (see, eg, McKinney et al, 2005;de Vrij et al, 2008;Gross et al, 2010;Grossman et al, 2010). Some findings are contradictory; for example, several studies have reported significantly increased total dendritic spine density in cultured hippocampal Fmr1 KO neurons as well as in cortex and olfactorial bulb in vivo (Hayashi et al, 2007;Gross et al, 2010;Liu et al, 2011;Scotto-Lomassese et al, 2011), whereas other studies have detected increased numbers of filopodia, but no significant difference in total spine density in the cortex in vivo and in cultured hippocampal neurons (Irwin et al, 2002;de Vrij et al, 2008;Bilousova et al, 2009). Different experimental settings, such as age of the mice or neuronal cultures, might explain variations in the observed phenotypes.…”
Section: Abnormal Dendritic Spine Morphology In Fxsmentioning
confidence: 99%